STUDI KASUS : USIA IBU SEBAGAI FAKTOR RISIKO TERJADINYA PLASENTA PREVIA Case Study : Maternal Age as a Risk Factor for Placenta Previa - Rosmiarti Rosmiarti (Masker Medika, 2024)
Introduction: Pregnancy is a process that begins with the arrival of the egg and sperm in the uterus, specifically in the fallopian tubes. Placerna previra is the closure of the cervix or all internal openings of the cervix by the placenta. Secondary vaginal bleeding caused by placerta previra can cause maternal death, hirsterectomy, postpartum hemorrhage that requires blood transfusions, maternal internal care, and cervical cancer. Methods: Primary analysis involves collecting subjective and objective data based on bird care during pregnancy. Results: The results of the study show that the transportation subject does not limit food, the daily activity pattern is within normal limits, the general condition is good and full of consciousness. Discussion: Risk factors related to previral placerta include parirtas, older births, smoking, cocaine use, history of infestation and postpartum history, history of assisted reproduction, history of cesarean surgery, and history of placenta previra.